Estudio de la arquitectura lírica en el contexto sur del Departamento del Huila para salvaguardar al Pueblo indígena Yanacona (2022)
The following research is developed in the south of the Department of Huila in the municipality of Palestina, which is the scene of the Yanacona indigenous people considered one of the oldest ancestral cultures of Colombia, facilitating the development of an investigative work that allows th e cultural and architectural conservation of the Yanacona indigenous people through the lyrical architecture, from this analysis a research question is developed which gives beginning and direction to the project, being this, How is the lyrical architectur e linked to the cultural and dialectic conservation of the Yanacona people in the south of the Department of Huila? Which seeks the articulation between architecture and the role it plays in cultural conservation, handling concepts of lyrical architecture, which strengthen the culture based on the worldview of the Yanacona people, for its preservation and dissemination through it helping to restore those elements of identity.